1987
DOI: 10.2165/00003088-198712060-00004
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of Bumetanide in Grossly Oedematous Patients

Abstract: A pharmacokinetic study was undertaken to determine the bioavailability of bumetanide in grossly oedematous patients. Six nephrotic patients were administered bumetanide 2mg orally (as tablets) and intravenously as single doses, in a randomised fashion. Serum bumetanide concentration-time profiles were characterised. Data were fitted to a 2-compartment model (5 patients) and a 3-compartment model (1 patient). Analysis of the areas under the curves showed a bioavailability of 0.84 +/- 0.2, which is similar to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…These findings of an overall potency ratio P/F of approximately 6:40, on a weight to weight basis, is in agreement with other reports of relative potency ratios for comparative short-term studies (Clissold & Brogden, 1985). In previous reports from this laboratory the bioavailability of piretanide in patients with severe CCF was found to be 68 ± 7% (n = 3) compared with 79 ± 6% (n = 4) in normal subjects (McNabb et al, 1984b (Bailie et al, 1987). (84.0 ± 9.9 mmol mg-1; n = 13; P < 0.01, unpublished observations).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…These findings of an overall potency ratio P/F of approximately 6:40, on a weight to weight basis, is in agreement with other reports of relative potency ratios for comparative short-term studies (Clissold & Brogden, 1985). In previous reports from this laboratory the bioavailability of piretanide in patients with severe CCF was found to be 68 ± 7% (n = 3) compared with 79 ± 6% (n = 4) in normal subjects (McNabb et al, 1984b (Bailie et al, 1987). (84.0 ± 9.9 mmol mg-1; n = 13; P < 0.01, unpublished observations).…”
Section: Resultssupporting
confidence: 92%
“…While there was no change in tmax (time for maximal plasma concentration), the Cmax (maximum plasma concentration) tended to be lower in the cardiac failure group, the mean values were, however, not significantly different from those obtained in normajs [tma (min) 60 ± 12 (n = 4) vs 58 ± 6 (n = 13) and Cmax (ng ml-) 189 ± 36 (n = 4) vs 273 ± 38 (n = 13) respectively (unpublished observations)]. A recent report has shown that oral bioavailability of bumetanide, a closely related sulphamoylbenzoate diuretic, is not diminished in grossly oedematous patients (Bailie et al, 1987).…”
Section: Discussionmentioning
confidence: 78%
“…A recent study from our laboratory reports fewer hospitalizations and better quality of life in patients with heart failure treated with a completely absorbed loop diuretic as represented by torsemide compared with furosemide (67). Edematous disorders do not cause malabsorption of loop diuretics (6,13,18,34,86,91,94,95). Absorption is slowed, particularly in patients with decompensated heart failure (95), but the total amount absorbed is the same as in healthy individuals.…”
Section: Pharmacokinetcs Of Loop Diureticsmentioning
confidence: 99%
“…In patients with congestive heart failure and preserved renal function, delivery of loop diuretics to the tubular fluid is normal (5,39,74). Historically, the possibility has been raised that patients with overt heart failure likely have gut wall edema causing diuretic malabsorption; studies have shown that the same quantity of loop diuretic is absorbed in such patients as occurs in healthy control subjects (6,13,92,95). Thus malabsorption does not occur.…”
Section: Pharmacodynamics Of Loop Diuretics In Edematous Disordersmentioning
confidence: 99%
“…8,9 In contrast, bumetanide and torsemide are less affected by intestinal wall edema, allowing for higher and more predictable bioavailability ranging from 80% to 100%. 8,10 Once in the blood, concentration kinetics also differ; furosemide and bumetanide have half-lives of 1 to 3 hours and a 6-to 8-hour duration of action, and torsemide has a longer half-life at 4 to 6 hours, with a 12-to 18-hour duration of action. 8,11 Compared with other loop diuretics, torsemide intrinsically blocks sympathetic nervous system and aldosterone activity, which may lead to favorable cardiac remodeling and decreased kaliuresis.…”
Section: Diuretic Therapymentioning
confidence: 99%